Intra-regional and long-range ragweed pollen transport over southern Hungary - Makra László (Acta climatologica, 2007)
A tanulmány célja, hogy a hossztú távú parlagfű pollen szállítás szerepét elemezze Szeged fölött, Délmagyarország térségében a napi pollenkoncentrációk 15 éves (1989-2003) adatbázisa alapján. A szállított és a helyi eredetű parlagfű pollen szemeket oly módon választottuk szét, hogy a helyi parlagfű virágzása előtt mért parlagfű koncentrációkat nem helyi eredetűnek tekintettük. Ezt követően elemeztük egyrészt a helyi parlagfű virágzása előtti időszak három legnagyobb pollenterhelésű napjának, másrészt a vizsgált időszak három legnagyobb átlagos pollenterhelésű napjának három- és hétnapos, időben visszafelé számított (backward), trajektóriáit. A fenti kiválasztott napokra alkalmaztuk a HYSPLIT-modellt azon célból, hogy kiszámítsuk a parlagfűpollen szemek trajektóriáit, s meghatározzuk azok forrásterületeit. A kapott trajektóriák azt mutatják, hogy amikor nincs helyi pollenszórás Délmagyarország térségében, akkor a Rhőne-völgyéből (Franciaország), Észak-Olaszországból és Horvátországból érkezhet parlagfű pollen Délmagyarország fölé. Másrészről, a három legsúlyosabb átlagos pollenterhelésű nap mindegyikének a trajektóriái áthaladnak a Duna-Tisza köze fölött, ami parlagfűvel és pollenjével az egyik leginkább fertőzött területnek számít Magyarországon. Következésképp, a legsúlyosabb pollenterhelésű napokon a szállított pollen tovább emelheti Délmagyarország fölött a levegő pollenkoncentrációját. Summar y - The aim of the study was to analyse the role of long-range transport of ragweed pollen over Szeged City, Southern Hungary on the basis of the daily pollen levels for the 15-year period between 1989-2003. Transported and local pollen grains were separated; ragweed pollen levels measured before the blooming of local ragweed were considered to be of transported origin. Then, 3-day and 7-day backward trajectories belonging partly to the three days having the highest pollen levels before the blooming period of ragweed and partly belonging to the three days having the highest average peak concentrations in the period were examined. For the days selected above, the HYSPL1T model was applied in order to calculate trajectories of airborne ragweed pollen grains, as well as to detect their source areas. The resulting trajectories show that when there is no release of ragweed pollen grains in Szeged and its surroundings, then ragweed pollen may come over the Szeged region from the Rhönevalley (Southern France), Northern Italy and Croatia. On the other hand, each of the trajectories, belonging to the three days having in average the three highest pollen levels during the 15-year period examined (1989-2003), passes through the region between the rivers Danube and Tisza, considered to be one of the areas most polluted with ragweed pollen in Hungary. Hence, transported pollen on the most heavily polluted days can further raise the airborne ragweed pollen concentrations over Southern Hungary.